2020
DOI: 10.3399/bjgp20x712781
|View full text |Cite
|
Sign up to set email alerts
|

Natural history of uncomplicated urinary tract infection without antibiotics: a systematic review

Abstract: BackgroundAlthough uncomplicated urinary tract infection (UTI) is commonly treated with antibiotics, the duration of symptoms without their use is not established; this hampers informed decision making about antibiotic use.AimTo determine the natural history of uncomplicated UTI in adults.Design and settingSystematic review.MethodPubMed was searched for articles published until November 2019, along with reference lists of articles identified in the search. Eligible studies were those involving adults with UTIs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 15 publications
0
25
0
Order By: Relevance
“… 10 11 Thus, the lower yield of urine cultures in this study may be due to spontaneous resolution of infection because of the delays in accessing healthcare or self-treatment with antibiotics. 15 This may particularly be the case in patients with leucocyturia where symptoms can be explained by residual inflammation. Dysuria and leucocyturia in the absence of positive urine cultures may be due to other causes such as urogenital tuberculosis, schistosomiasis and other inflammatory conditions.…”
Section: Discussionmentioning
confidence: 99%
“… 10 11 Thus, the lower yield of urine cultures in this study may be due to spontaneous resolution of infection because of the delays in accessing healthcare or self-treatment with antibiotics. 15 This may particularly be the case in patients with leucocyturia where symptoms can be explained by residual inflammation. Dysuria and leucocyturia in the absence of positive urine cultures may be due to other causes such as urogenital tuberculosis, schistosomiasis and other inflammatory conditions.…”
Section: Discussionmentioning
confidence: 99%
“…In line with other studies symptom resolution or improvement was common even in those participants who did not take effective treatment. Spontaneous symptom resolution of uncomplicated cystitis occurs in about a third of patients 9 . However, patients without spontaneous cure often experience debilitating symptoms that can persist for several weeks 10 , affecting quality of life 11 and leading to economic costs due to loss of income, missed days at work and medical expenses 1,12,13 .…”
Section: Discussionmentioning
confidence: 99%
“…Hoffmann et al reviewed the natural course of uncomplicated UTI in women on studies up to November 2019, they found only three placebo-controlled randomized trials and reported symptoms duration. (19) Their results showed that complete symptom recovery could occur in 18% (up to 3 days) to 54% (up to 6 weeks) of the placebo arm, with most improvement occurring in the first 9 days. These findings are in line with our results as we found symptoms were completely resolved within the study follow up in nearly two thirds (62%) of the women who did not consume antibiotics.…”
Section: Comparison With Existing Literaturementioning
confidence: 98%